TiO2: CuO and TiO2: ZnO/ paraffin wax as Nano composites: synthesis and investigation as solar energy cells and corrosion inhibitors - Hasan, Tabarak Saad; Al-Abdaly, Basim Ibrahim (Iraqi Journal of Science, 2025)
In this study , nanoparticles of the metal oxides CuO, ZnO, and TiO2 were synthesized using the hydrothermal method. These nanoparticles were then used to dope paraffin wax (as the matrix material) and prepare nanocomposites [TiO2; CuO/paraffin] and [TiO2; ZnO/paraffin] through the ultrasound method. The morphology, size, and structures of the synthesized nanocomposite were examined and characterized using atomic force microscopy (AFM), X-ray diffraction (XRD), Fourier and transform infrared (FT-IR), in order to confirm the design of nanocomposite based nanostructures and reveal their distinctive features from where distribution on paraffin wax. The results of AFM analysis of the two synthesized nanostructure, [TiO2; CuO/paraffin] and [TiO2; ZnO/paraffin], revealed that the size of the nanoparticles was within the nanoscale range, measuring 49.54 nm and 57.16 nm, respectively. Their grooves in all nanostructures of the synthesized composites are heterogeneous as depicted by three-dimensional images, this is mainly caused by the agglomeration of metal oxide nanoparticles which leads to coverage of some of the paraffin surface. The activities of Nano composites synthesized were studied from the industrial side, including solar cell energy and the use of these Nano composites as inhibitors for corrosion. The findings for all of these nanocomposite revealed they have the properties of solar cells and a significant inhibitory effect.